TINJAUAN TERHADAP PEMANFAATAN ALAT PERMAINAN EDUKATIF (APE) OLEH GURU DI TK AL-AZHAR SIEM - Nurul Khaira; Suhartati .; Rosmiati .; Bahrun .; Mutmainnah . (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2022)
Keywords: Educational Playing Tools, Teachers This study aims to determine the use of Educational Game Tools by teachers at Al-Azhar Siem Kindergarten. The method used is descriptive qualitative research method by taking three (3) teachers in class B1, B2, and B3. Furthermore, the data collection techniques in this study were observation and interviews. The results showed that teachers at Al-Azhar Siem Kindergarten, namely S1, S2, and S3 have been able to utilize Educational Game Tools well in the learning process. The use of Educational Game Tools carried out by teachers consists of (1) teachers using Educational Game Tools in the learning process and Educational Game Tools used by teachers can support 6 aspects of children's development (2 ) the availability of Educational Game Tools to support the growth and development of children aged 5-6 years at Al-Azhar Siem Kindergarten is good although there are still some Educational Game Tools that are not available (3) Educational Game Tools used by the teacher is in accordance with the learning theme and the age and condition of the child (4) the teacher also provide motivation and guidance to children when playing Educational Game Tools (5) the use of Educational Game Tools by teachers in supporting 6 aspects of child development is good because the teacher follows the procedures for using Educational Game Tools including: preparation, implementation, evaluation and follow-up stages. This research is expected to add insight to kindergarten teachers in utilizing Educational Game Tools properly and appropriately. Abstrak. Penelitian ini bertujuan untuk mengetahui pemanfaatan Alat Permainan Edukatif (APE) oleh guru di TK Al-Azhar Siem. Metode yang digunakan adalah metode Penelitian deskriptif kualitatif dengan mengambil 3 guru di kelas B1, B2, dan B3. Selanjutnya, teknik pengumpulan data dalam penelitian ini adalah observasi dan wawancara. Hasil penelitian menunjukkan bahwa guru di TK Al-Azhar Siem yaitu S1, S2, dan S3 telah mampu dalam memanfaatkan APE dengan baik pada proses pembelajaran. Adapun pemanfaatan APE yang dilakukan oleh guru terdiri dari (1) guru memanfaatkan APE pada proses pembelajaran serta APE yang digunakan oleh guru dapat menunjang 6 aspek perkembangan anak (2) tersedianya APE untuk mendukung tumbuh kembang anak usia 5-6 tahun di TK Al-Azhar Siem bagus walaupun masih ada beberapa APE yang tidak tersedia (3) APE yang digunakan oleh guru sesuai dengan tema pembelajaran serta usia dan kondisi anak (4) guru juga memberikan motivasi dan bimbingan kepada anak ketika memainkan APE (5) pemanfaatan APE oleh guru dalam menunjang 6 aspek perkembangan anak baik karena guru mengikuti tata cara penggunaan APE meliputi: tahap persiapan, pelaksanaan, evaluasi dan tindak lanjut. Penelitian ini diharapkan dapat menambah wawasan kepada guru TK dalam memanfaatkan APE dengan baik dan tepat. Kata Kunci: Alat Permainan Edukatif (APE), Guru